Journalism and media competencies: an approach from a Colombian and Ecuadorian context - Montoya Ramírez, Nélida (2020)
This article presents the results of a descriptive quantitative exploratory study conducted in the countries of Colombia and Ecuador to assess the degree of media competence of 146 journalists from the cities of Medellín (Colombia) and Loja (Ecuador). A self-administered questionnaire was applied, structured with nine sociodemographic questions, four on the generalities of the level of media competence and 24 evaluative distributed in the six dimensions of this type of competition with their respective indicators. The general results of low and medium-level competition obtained by this group of professionals demand priority interventions from local, regional and international works that mobilize scientific, academic and political cooperation to improve the performance of a population that should lead the general formation of the citizenship in media competitions.